Utilizing rice husks by moderately halophilic Bacillus spp. isolated from Sawa Lake as a carbon source - Adnan H. Abbas; Muntaha A. Al-Safar; Zeyad Gattea Al-Rikabi; Eman H. Abed (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Rice husk is a sustainable, plentiful, and cheap resource with great potency for bioconversion to important bioproducts. This process required suitable employment of active pretreatment and hydrolysis enzymes to produce reduced sugars. Five isolates (AE1, AE2, AE3, AE4, and AE5) of moderately halophilic Bacillus were isolated from Sawa Lake, which is resistant to 12% sodium chloride. Results showed that isolates (AE1, AE3, and AE4) produce cellulase enzymes. AE3 isolate chooses to produce cellulase after being cultured in nutrient broth supplemented with 1% of pretreatment rice husk and incubated for (4, 7, 11, 18, and 21) days at 30°C with rotation 150rpm, with activity (48.08, 109.38, 68.77, 68.16 and 41.42) U/ml, the concentration of cellulose residue (125, 97.4, 106.4, 122.7 and 142.9) µg/ml, respectively. These results prove that the cellulose component of pretreatment rice husk was consumed and increased up to 7days of incubation period at 30°C with a rotation of 150rpm.